A systems biology approach to define SARS-CoV-2 correlates of protection in non-human primates - Brady, C (2024)
SARS-CoV-2 is expected to become a seasonal human coronavirus, with annual vaccination advised for vulnerable populations, similar to influenza. Unlike influenza, correlates of protection (CoPs) for SARS-CoV-2 have yet to be defined, which will impede the approval of new vaccines. Here, we present the largest known compilation of SARS-CoV-2 macaque challenge studies to date (n=90) that uniquely used both viral load and lung histopathology as criteria for protection from challenge. Evidence from the literature in favour of spike humoral responses predicting protection in humans, prompted the investigation into macaque humoral response characteristics, and the factors that contribute to humoral response development. The relationship between spike antibody isotype, IgG subclass, glycosylation and functional responses, and the relationship between these properties and protection, was explored. Using the machine learning platform, SIMON, pre-challenge immune predictors of clinical and viral protection were identified in immunised macaques, which included binding and neutralising antibody. Novel predictors of protection included low peripheral intermediate monocyte prevalence during the vaccination regimen and low seasonal coronavirus IgG at baseline - parameters which also predicted high spike IgG titres post- vaccination. These results contribute to SARS-CoV-2 CoP definition and shed light on the factors influencing the success of SARS-CoV-2 vaccination.